Answer:
B) 
Step-by-step explanation:
Because
simplifies to
, we only care about the quotient, which will be our oblique asymptote equation. Therefore, the oblique asymptote for the function will be
. See the attached graph for a visual.
Answer:
m= -1
I hope this helped, have a great day!! <3
Factor out the common term 4
-4(2x - y) = 24
Divide both sides by -4
2x-y= - 24/4
Simplify24/4 to 6
2x -y = -6
Subtract 2x from both sides
-y = -6 - 2x
Multiply both sides by -1
y = 6 + 2x
Answer:
2 7/8
Step-by-step explanation: